Analisis Komplikasi Operasi Katarak Terhadap Pasien Katarak - A.Tenri Ola; Sri Irmandha Kusumawardani; Azizah Anoez (Universitas Muhammadiyah Manado, 2024)
Cataracts are the most common cause of blindness in the world. About 90% of cataract cases are age-related, other causes are congenital and trauma. The definitive treatment for cataracts is surgery. Several cataract surgery techniques are increasingly developing with smaller incisions, fast healing, and low complication rates. Periodic examination after cataract surgery is very important to detect complications. This literature review study aims to determine the description of cataract surgery complications. The journal in this literature review uses 3 databases including Google Scholar, PubMed, and Science Direct using the keywords complications of cataract surgery and complications of cataract surgery. The literature search was adjusted based on inclusion and exclusion criteria. The search results obtained 10 journals consisting of 5 national journals and 5 international journals. The results show the types of cataract surgery complications, namely Irregular Pupil/anisocoria, Posterior Capsule Rupture (PCR), Vitreous loss, Hyphaema, Iris Prolapse, Vitreous Prolapse, Iris Prolapse, Traumatic Iris, Descemet's Membrane Detachment (DMD), Retinal Detachment, Posterior Capsule Opacity ( PCO), Intraocular Lens Malposition (LIO), Cystoid Macular Edema (CME), Pseudophakic Bullous Keratopathy (PBK), Increased Intraocular Pressure (IOP), Iridodialysis, Surgically Induced Astigmatism (AIS), Cystoid Macular Edema (EMK), Uveitis, Dry Eye Syndrome, Corneal Edema, Anterior Segment Toxic Syndrome, Ocular Hypertension, Endophthalmitis, Zonular dehiscence.